Persepsi Mahasiswa Pendidikan Matematika terhadap Penggunaan AI Tools dalam Pemecahan Masalah - Amini, Aisyatul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The growth of artificial intelligence (AI) has led to its use in education, especially in learning math. This study looks at how math education students at PGRI Wiranegara University feel about using AI tools to solve math problems. The study used a quantitative method with a descriptive approach. It included 20 students from the 2022 group who were chosen because they had used AI tools before. The main tool used in the study was a questionnaire that measured students' perceptions on a five-point scale. The questionnaire focused on areas like the benefits of AI, how easy it is to use, its effect on problem-solving, and any challenges in using AI. The data was analyzed using descriptive statistics. The results showed that students had a positive view of using AI tools because they found them helpful in understanding math concepts, organizing steps to solve problems, and making learning more efficient. Students also thought AI tools were easy to use and helped them with solving math problems. However, some challenges were noted, like limited internet access and worries about less independent thinking. Even with these issues, students still saw AI as a helpful tool for learning. The study concludes that AI can be a good support for math learning if used in a smart and thoughtful way.